Pengembangan Modul Berbasis Eksperimen untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Kelas V SDN 122 Rejang Lebong - Rara Oktaviana; Dalifa Dalifa; Panut Setiono (JURIDIKDAS, 2022)
AbstractThe purpose of this study was to develop the experiment-based module to improve the critical thinking skills of fifth grade students at SD Negeri 122 Rejang Lebong which can be used as a guide for teachers. This research is a Research and Development (R&D) with a modification of the 4-D model, but in this study it was only carried out until the third stage, namely define, design and develop. This experiment-based module is validated by materials experts, design experts and linguists. The module developed was responded to by two teachers of SD Negeri 122 Rejang Lebong. The data analysis technique used descriptive statistical analysis, namely the results of expert validation assessments, teacher responses, and student trials, as well as qualitative descriptive analysis of expert validation comments and teacher responses. This study resulted in an experiment-based module to improve critical thinking skills with a material expert assessment of 91.35 in the very valid category, 96 linguists validation in the very valid category, 96 design validation in the very valid category, and the teacher's response of 96 in the very good category. used as the final product of development. The results of the pretest and posttest trials of students obtained a score range of 0.5 with a medium category, meaning that the developed module can improve the critical thinking skills of fifth grade students of SD Negeri 122 Rejang Lebong.Keywords : Module, Experiment, Critical Thinking Skills